ML driven models to predict the drag coefficient of a sphere translating in shear-thinning viscoelastic fluids - Roriz, Ana Isabel Araújo (2021)
Apresentação efetuada no 17th International Conference of Computational Methods in Sciences and Engineering (ICCMSE 2021), em Crete, Greece, 2021